1985
DOI: 10.1111/j.1751-1097.1985.tb01557.x
|View full text |Cite
|
Sign up to set email alerts
|

REPAIR OF UV‐IRRADIATED PLASMID DNA IN EXCISION REPAIR DEFICIENT MUTANTS OF Saccharomyces cerevisiae

Abstract: Abstract— The repair of UV‐irradiated DNA of plasmid Yep13 was studied in the incision defective strains by measurement of cell transformation frequency. In Saccharomyces cerevisiae, radl,2,3 and 4 mutants could repair UV‐damaged plasmid DNA. In Escherichia coli, uvrA mutant was unable to repair UV‐damaged plasmid DNA; however, pretreatment of the plasmid with Micrococcus luteus endo‐nuclease increased repair. We concluded that all the mutations of yeast were probably limited only to the nuclear DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…It is interesting to note here that identical results were obtained by other laboratories with radl-1 mutants and UV-incoming DNA (White and Sedgwick, 1985;Dominski and Jachymczyk, 1987). However, Ikai et al (1985) reported that the radl-2 mutant had a normal capacity to repair UVincoming DNA although the mutant was sensitive to UV. This may indicate that the repair of UVincoming DNA varies somewhat between different RADI alleles.…”
Section: Host Repair Processes Remove Uv Damage In the Incoming Dnasupporting
confidence: 88%
See 2 more Smart Citations
“…It is interesting to note here that identical results were obtained by other laboratories with radl-1 mutants and UV-incoming DNA (White and Sedgwick, 1985;Dominski and Jachymczyk, 1987). However, Ikai et al (1985) reported that the radl-2 mutant had a normal capacity to repair UVincoming DNA although the mutant was sensitive to UV. This may indicate that the repair of UVincoming DNA varies somewhat between different RADI alleles.…”
Section: Host Repair Processes Remove Uv Damage In the Incoming Dnasupporting
confidence: 88%
“…the plasmid survival was different from that found in the RAD+ host. The mutants rad2-6 (Ikai et al, 1985) and rad2 (Dominski and Jachymczyk, 1987) were able to repair UV-incoming DNA as well as the parental RA D + strains. Although different plasmid DNAs, transformation procedures and other experimental conditions were used, the differences between alleles should be further investigated.…”
Section: Host Repair Processes Remove Uv Damage In the Incoming Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, other rad3 mutant alleles were not examined by these authors. Similarly surprising results were reported by Ikai et al (101), who measured transformation frequencies for various rad mutants transfected with a UV-irradiated multicopy plasmid. They noted that, relative to a wild-type strain, transforma-tion was unaffected in the rad3-2 strain and also in radl-2, rad2-6, and rad44 strains.…”
Section: Plasmids To Monitor Nucleotide Excision Repairsupporting
confidence: 79%
“…White and Sedgwick (282) noted that the UV sensitivity of the rad3-2 strain reported by Dominski and Jachymczyk (41) was significantly less than that expected and suggested that the rad3-2 strain used by the latter authors may have accumulated suppressors. However, there is no obvious explanation for the results of Ikai et al (101), and the use of plasmids for probing the molecular biology of excision repair in S. cerevisiae may involve experimental artifacts that remain to be identified.…”
Section: Plasmids To Monitor Nucleotide Excision Repairmentioning
confidence: 99%